(untitled) - Theary, Pok (Can Tho, 2017)
Contents: Effect of soaking biochar in biodigester effluent as soil improver on soil characteistics and yield of water spinach (Ipomoea aquatica)
Keywords: Thức ăn gia súc,Animal feeding